Bahasa Inggris - Herdi, Herdi; Mamesah, Michiko (VISI : Jurnal Ilmiah Pendidik dan Tenaga Kependidikan Pendidikan Non Formal, 2023)
Self-compassion is one of the adaptive self-attitudes that can be used by adolescents who experience personal dissonance or facing difficult situations and implemented as a normal experience of adolescents who drugs abuse. However, studies on standardized instruments and self-compassion profiles of drug abusers in Indonesia are still limited. Therefore, an intensive study of standardized instruments is needed to measure the compassion of adolescent drug abusers. This study uses an adaptation of a instrument procedures. As many of 38 as teenage drug users of six Social Rehabilitation Foundations in Indonesia. Data is measured using Self-Compassion Scale-Short Form. Operationally, the data analysis used Rash Model 3.75. The results showed that SCS-SF has satisfactory psychometric properties. Further studies are required to examine the psychometric properties of the SCS-SF of various participant socio-demographic factors.